Evaluation of peri-implant soft and hard tissues around dental implants placed at the Faculty of Dentistry, UiTM / Mohd Faizal Hafez Hidayat ... [et al.] - Hidayat, Mohd Faizal Hafez; Kamar Affendi, Nur Hafizah; Hasirin, Rosharina Azian; Wan Mohd Noor, Wan Anis Sufiah (2019)
This study is carried out to assess the soft and hard tissue conditions around dental implant cases at the Faculty of Dentistry Universiti Teknologi MARA (UiTM). Methods: Patients with dental implants of more than 6 months in function were recalled for clinical and radiographic evaluation. Probing pocket depth, suppuration, bleeding, recession and plaque index were clinically evaluated. Periapical radiograph (IOPA) were also taken. The data from the findings were statistically evaluated using SPSS program. Result: 14.3% of implants placed in consider healthy, 4.8% implants have clinical stability and 81% have peri-implant mucositis and none of the participants have peri-implantitis and severe peri-implantitis. Conclusion: Within the limitation of this study, it's concluded that the status of peri-implant tissues is mainly affected by gender, systemic disease, smoking status,oral hygiene and years of implants functioning in oral condition. In addition, age plays a significant role that contribute to periimplant health.